Penguatan Jiwa Wirausaha Santri Melalui Program Pendampingan Berbasis Strategi Praktis Di Pesantren Modern Al-Izzah As'adiyah As'adiyah Tolai - Muhsyanur; Syamsul Bahri; Syamsuddin Semmang; Hasriadi; Umrati; Mansur (Universitas Merdeka Surabaya, 2025)
The entrepreneurial spirit strengthening program for students at Modern Islamic Boarding School Al-Izzah As'adiyah Tolai was implemented to integrate Islamic values with entrepreneurial competencies. This activity aims to equip students with practical entrepreneurial skills through intensive mentoring based on measurable strategies. The method used is participatory mentoring with an experiential learning approach. Results show that 85% of students experienced increased entrepreneurial motivation and 70% were able to develop simple business plans. This program successfully created a sustainable entrepreneurial ecosystem within the boarding school environment. Recommendations for development include adding micro-business capital and establishing a student business incubator.